Coping with psychosis and schizophrenia family stories of hope and recovery - Kuipers, Liz; Onwumere, Juliana; Shiers, David (Cambridge University Press, 2024)
Supporting a relative living with a psychotic disorder can be uniquely challenging when compared to other health conditions, leaving many family carers isolated and struggling with questions: Why us? How do others cope? Is it my fault? How much more can I take? This collection of personal accounts provides family carers with a helpful framework to make sense of their individual experiences and support their own coping and wellbeing. It details the myriad of positives, challenges and life-changing experiences that families encounter following the development of a psychotic illness in a loved one. The authors of these accounts are varied and include the parents, partners, siblings and children of those experiencing psychosis. This book will also serve as an excellent resource for psychiatrists, psychiatric nurses, psychologists, social workers, GPs and students who should find the book relevant both for their own practice and for those families they support.